2001
DOI: 10.1016/s0735-1097(01)01313-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in QRS voltage in cardiac tamponade and pericardial effusion: reversibility after pericardiocentesis and after anti-inflammatory drug treatment

Abstract: Low QRS voltage is a feature of cardiac tamponade but not of pericardial effusion per se. Our findings indicate that the presence and severity of cardiac tamponade, in addition to inflammatory mechanisms, may contribute to the development of low QRS voltage in patients with large pericardial effusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 13 publications
0
37
1
4
Order By: Relevance
“…Although there was a significantly higher incidence of PE in these patients compared to those without low voltage, the presence of PE was not an independent variable related to low voltage in the multivariate analysis. Bruch et al [26] reported that not only the presence of large PE but also the inflammatory mechanisms contributed to the occurrence of low voltage. Therefore, our data are consistent with previous reports that serous pericardial fluid retention is not essential for the presence of low voltage on the surface ECG.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was a significantly higher incidence of PE in these patients compared to those without low voltage, the presence of PE was not an independent variable related to low voltage in the multivariate analysis. Bruch et al [26] reported that not only the presence of large PE but also the inflammatory mechanisms contributed to the occurrence of low voltage. Therefore, our data are consistent with previous reports that serous pericardial fluid retention is not essential for the presence of low voltage on the surface ECG.…”
Section: Discussionmentioning
confidence: 99%
“…1 Limbs leads low voltage is not uncommon in clinical practice and its differential diagnosis includes conditions such as obesity, lung emphysema, pericardial effusion, hypothyroidism and amyloidosis. Low voltage of the precordial leads is less common than limbs leads voltage and might be a feature of cardiac tamponade 2 or appear temporarily after defibrillation or cardioversion. 3 Little is known about the prevalence of low voltage in patients with ascites.…”
Section: Introductionmentioning
confidence: 99%
“…Baixa amplitude do QRS acontece na presença de derrame pericárdico, que melhora após pericardiocentese 189,190 . A alternância na morfologia ou amplitude do QRS está associada à pericardite com derrame pericárdico volumoso e sinais de tamponamento cardíaco 191 .…”
Section: Diretriz Brasileira De Miocardites E Pericarditesunclassified